STRATEGIC AGRICULTURAL MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT CONCEPT - Shkolnyi, Oleksandr (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The problems of strategic agricultural management in the context of sustainable development are investigated, with emphasis on the integration of innovative and digital technologies into agri-food production processes. The principles of implementing innovative technologies of precision agriculture, artificial intelligence and human capital formation to increase the efficiency, environmental sustainability and competitiveness of agricultural enterprises in a global context are considered.